(untitled) (Asian Journal of Social Science Studies, 2017)
With the development of society, for application of the disciplines of art and design, the ability of "art + technology" is to develop the inevitable demand for the development of the times. Then, how to learn within four years of university studies, so that students can master good artistic and technical skills? This article combines with teaching practices from the perspective of setting up of the curriculum system and teaching by engineers outside the school. The aim is to meet the social needs of the subject training so as to explore the visual communication of professional education reform, with its professional education research to provide reference.